2022
DOI: 10.1037/pspa0000298
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness meditation reduces guilt and prosocial reparation.

Abstract: The present research investigates whether and how mindfulness meditation influences the guilt-driven tendency to repair harm caused to others. Through a series of eight experiments (N > 1,400), we demonstrate that state mindfulness cultivated via focused-breathing meditation can dampen the relationship between transgressions and the desire to engage in reparative prosocial behaviors. Experiment 1 showed that induced state mindfulness reduced state guilt. Experiments 2a–2c found that induced state mindfulness r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 155 publications
(270 reference statements)
5
47
0
Order By: Relevance
“…In particular, what is the mechanism causing people in this condition to improve in these ways? One conclusion is perhaps our intervention reduced participants' overall guilt, and thus promoted increased sensations of satisfaction with their daily experiences (Hafenbrack et al. , 2021).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In particular, what is the mechanism causing people in this condition to improve in these ways? One conclusion is perhaps our intervention reduced participants' overall guilt, and thus promoted increased sensations of satisfaction with their daily experiences (Hafenbrack et al. , 2021).…”
Section: Discussionmentioning
confidence: 97%
“…As such, further research should investigate the potential unfavorable effects of mindfulness interventions. Research has suggested that, when state mindfulness is induced, one is less likely to feel guilt and this decrease in sensations of guilt can lead to decreased willingness to repair social interactions that are vital for satisfaction (Hafenbrack et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations